2017
DOI: 10.1126/scitranslmed.aaf8848
|View full text |Cite
|
Sign up to set email alerts
|

A divergent population of autoantigen-responsive CD4+T cells in infants prior to β cell autoimmunity

Abstract: Autoimmune diabetes is marked by sensitization to β cell self-antigens in childhood. We longitudinally followed at-risk children from infancy and performed single-cell gene expression in β cell antigen-responsive CD4 T cells through pre- and established autoimmune phases. A striking divergence in the gene signature of β cell antigen-responsive naïve CD4 T cells from children who developed β cell autoimmunity was found in infancy, well before the appearance of β cell antigen-specific memory T cells or autoantib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 56 publications
3
59
1
2
Order By: Relevance
“…A rapid progression to clinical T1D is indicative of multiple layers of tolerance defects and aberrant immune activation. However, despite recent insights into identifying a divergent autoantigen-responsive CD4 + T cell population in infants before developing islet autoimmunity (4), molecular underpinnings involved in triggering the onset of islet autoimmunity remain incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
“…A rapid progression to clinical T1D is indicative of multiple layers of tolerance defects and aberrant immune activation. However, despite recent insights into identifying a divergent autoantigen-responsive CD4 + T cell population in infants before developing islet autoimmunity (4), molecular underpinnings involved in triggering the onset of islet autoimmunity remain incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
“…TLR3 and IL-15 receptor subunit α (IL15RA), which increase NF-κB signaling-mediated immune activation and promote memory T cell differentiation, respectively, were downregulated in blood of nonseroconvertors during the first year. A recent temporal study of antigen-responsive CD4 + T cells in children from the BABYDIET cohort also identified the development of T cell memory concomitant with autoantibody development (25). Patched 1 (PTCH1), which was upregulated in blood of seroconverters over time, is required for development of the T and B lymphoid lineages (26).…”
Section: Discussionmentioning
confidence: 99%
“…Patched 1 (PTCH1), which was upregulated in blood of seroconverters over time, is required for development of the T and B lymphoid lineages (26). Some of the DE genes are known to be important coordinators of diverse developmental processes (e.g., Sprouty RTK signaling antagonist 1 [SPRY1)]), and although likely to have important functions in circulating immune cell populations, their specific functions are still to be elucidated (25). Adrenoreceptor β 2 (ADRB2) and adenylate cyclase 9 (ADCY9) gene expression data further suggest that β adrenergic signaling pathways may also differentiate children who are likely to seroconvert.…”
Section: Discussionmentioning
confidence: 99%
“…This is the basis of the hygiene hypothesis that argues that the absence of a range of infections in early childhood (worms, viruses, and other microbes) impairs maturation of the immune system, thereby affecting the lymphocytic repertoire, altering immunoregulation and increasing the risk of T1D [8]. In fact, perinatal environmental exposure is crucial for sensitizing to β-cell autoantigens and for developing a specific gene signature in autoreactive CD4 + T lymphocytes [9]. Overall, these data suggest that T1D is the consequence of a multistep process initiated during the early stages of life.…”
Section: T1d and Childhoodmentioning
confidence: 99%